PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT FOR THE FORMATION OF PROFESSIONALLY IMPORTANT QUALITIES OF INTERNAL AFFAIRS' OFFICERS OF THE RUSSIAN FEDERATION - Pavel Kushchev (Вестник Северо-Кавказского федерального университета)
The article reveals the essence and content ofpsychological and pedagogical support ofprofessional training of MIA employees. Much attention is paid to the analysis of problems and trends in the development of psychological and pedagogical support. Priorities of improvement of system of psychological and pedagogical support ofprofessional training of employees of the Ministry of internal Affairs are allocated, the characteristic of its structure and the main components is presented. The author proposes a model of psychological and pedagogical support of the formation of professionally important qualities of interior Ministry employees.